2016
DOI: 10.1002/osp4.77
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in Malta

Abstract: SummaryBackgroundObesity is a global epidemic with the Mediterranean island of Malta being no exception. The World Health Organization (WHO) has identified Malta as one of the European countries with the highest obesity prevalence.MethodA cross‐sectional study was conducted (2014–2016) under the auspices of the University of Malta. The prevalence of overweight‐obesity in Malta was calculated and then age stratified for comparisons with previous studies.ResultsThe study identified 69.75% (95% CI: 68.32–71.18) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…years old exhibiting the highest prevalence of overweight for both genders. 12 A study conducted on Chinese adults also revealed that the prevalence of overweight increased with age up to the age of 60, and it declined after that. 7 This can be due to having a more sedentary lifestyle and performing less physical exercises while getting older.…”
Section: Discussionmentioning
confidence: 98%
“…years old exhibiting the highest prevalence of overweight for both genders. 12 A study conducted on Chinese adults also revealed that the prevalence of overweight increased with age up to the age of 60, and it declined after that. 7 This can be due to having a more sedentary lifestyle and performing less physical exercises while getting older.…”
Section: Discussionmentioning
confidence: 98%
“…When assessing sex differences across age-groups, Maltese females exhibited the highest burden discrepancy from males after the age of 60. Possible explanations for this finding could be that LBP is associated with the onset of menopause and to the reported fact that female obesity prevalence is higher than their male counterparts in this age-group [ 19 ]. There were vast differences in estimates of DALYs for Malta when our study’s DALYs were compared to the GBD 2017 study estimates for the reference year 2015.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been postulated that underlying comorbidities and unhealthy lifestyle habits may be the reasons for this observation, where the male population tends to predominate (Wenham et al 2020;Purdie 2020). In fact, this is the case in Malta, where the male population has been reported to be more metabolically at risk than the female population, as seen in Table 1 (Cuschieri et al 2016a(Cuschieri et al , b, 2017(Cuschieri et al , 2018(Cuschieri et al , 2019Cuschieri 2020). Of concern is that a substantial proportion of the population (those with diabetes, obesity, cardiovascular disease) are at risk of acquiring complications if infected by COVID-19 (Fang et al 2020;Simonnet et al 2020).…”
Section: Malta and Covid-19mentioning
confidence: 99%